CORRELATION BETWEEN BODY FAT PERCENTAGE AND TOTAL CHOLESTEROL LEVELS TO HYPERTENSIVE ELDERLY WOMAN IN MADIUN - Binar Wahyuning Widhi; Mega Arianti Putri (Nurse and Health: Jurnal Keperawatan, 2021)
Background: Patients with hypertension have twice as great exposed to heart disease and eight times as large as a stroke risk than who do not experience hypertension. Risk increase in blood pressure on the person who has overweight than people with normal weight. Women who have increased cholesterol levels in the blood more vulnerable for hypertension (Nikolov et al., 2015). Objectives: The purpose of this research aimed to determine a percentage of body fat and cholesterol levels of the elderly women in Posyandu, Geger Subdistrict, Madiun who occurrence of hypertension. Methods: This research using cross sectional design. The sample using purposive sampling technique with 38 respondent which satisfy the inclusion criteria. Instrument used is Bioelectrical Impedance Analysis tool. Statistical test used is spearman rho with a significance level of ? < 0.05. Results: The results of this study showed that significant relationship between body fat percentage and blood pressure (p-value = .033; r = .304). Meanwhile, total cholesterol level did not show any relationship with blood pressure (p-value = .429; r = -.132). Conclusion: Fat Accumulation in the kidneys where the renin-angiotensin system is identified in human fat tissue, can cause impaired nephron function which causes blood pressure to rise. Thus, abdominal obesity accompanied by ectopic fat deposits can play an important role in the development of hypertension and should not be neglected when undertaking blood pressure-lowering therapy.